Proposta de mensuração dos canais de gestão de conhecimento: o caso da Procergs - Flach, Eduardo Sobreiro (Universidade do Vale do Rio dos Sinos, 2012)
Knowledge Management(KM) has become gradually the talk of the town since its advantages are perceivable, although many of them are non measureable.Supported by current innovation trends more and more companies consider knowledge as a diffential skill in competition and KM has been understood as a canalizer and motivational factor for innovation. This research has developed a unique case study in PROCERGS and intend to discover the channels whereabouts KM really flows in that company. Those channels are the ways where information is captured, organized and shared, digitally or conventionally as Forums, Internal blogs, external Motivational events, Electronic Document Management (EDM), Ideas Portals among others. Besides those channels studies a kind of categorization is created according to the Nonaka & Takeuch knowledge conversion model known as SECI (Socialization, Externalization, Combination, Internalization). This unique case study is a qualitative reasearch that used direct observation, documents analysis and interviewing KM Managers in collecting data. As result, a channel by channel descriptive analysis is generated, with its relationship with explicit and tacit knowledge and its rating according to the SECI Model. At last, a proposal is suggested in terms of a channel dashboard, so KM evolution conducters in the studied company can follow and leverage knowledge multiplying
Keywords: Gestão do Conhecimento; Mensuração; Conhecimento tácito e explícito; Knowledge; Management; Measuring